2011
DOI: 10.1098/rstb.2011.0033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vaccines against enteric infections: a clinical and public health research agenda for developing countries

Abstract: Enteric infections are a major cause of morbidity and mortality in developing countries. To date, vaccines have played a limited role in public health efforts to control enteric infections. Licensed vaccines exist for cholera and typhoid, but these vaccines are used primarily for travellers; and there are two internationally licensed vaccines for rotavirus, but they are mainly used in affluent countries. The reasons that enteric vaccines are little used in developing countries are multiple, and certainly inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…A sialidase-sensitive group A porcine RV OSU strain (P9 [7], G5) was obtained from the American Type Culture Collection. The virus was propagated in MA-104 cells as described previously (17) .…”
Section: Rotavirus Preparationmentioning
confidence: 99%
“…A sialidase-sensitive group A porcine RV OSU strain (P9 [7], G5) was obtained from the American Type Culture Collection. The virus was propagated in MA-104 cells as described previously (17) .…”
Section: Rotavirus Preparationmentioning
confidence: 99%
“…The high infection rates and rapid transmission between humans contribute to the significant morbidity associated with enteric viruses [ 4 ]. The absence of specific vaccines for human enteric viruses (except HRVs) further enhances the risk of infection [ 5 ]. More importantly, exposure to enteric virus-contaminated environments and/or drinking water, are generally thought to be responsible for a large proportion of outbreaks of waterborne diseases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…An expert panel convened by the Child Health and Nutrition Research Initiative (CHNRI) of the World Bank identified Shigella one of the highest priorities for long-term vaccine development [ 64 ]. In practice, the greatest impact on mortality of enteric vaccines, like Shigella, will be seen in medically underserved populations [ 65 ] and a safe, effective, and practical Shigella vaccine would likely save tens of thousands of lives and prevent hundreds of thousands of diarrheal illnesses in the developing world and in international travelers. Limited field trials of early live attenuated vaccine candidates or more recently, trials of polysaccharide based conjugate vaccines have shown vaccination to be a potentially effective public health tool in disease prevention and control [ 39 , 40 ] but currently there are no commercial products in the market.…”
Section: Discussionmentioning
confidence: 99%